2016
DOI: 10.1051/limn/2015027
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Does mosquito control by Bti spraying affect the phytoplankton community? A 5-year study in Camargue temporary wetlands (France)

Abstract: This article is a corrigendum of a former version by Fayolle et al., originally published in Ann. Limnol. -Int. J. Lim. 51: 189-198, 2015. In its original form, the article contained portions of text that were identical to Duguma et al., J. Appl. Ecol. 52: 763-773, 2015, similarities that were not detected by our plagiarism detection software upon initial submission of Fayolle et al.'s manuscript. Based on independent investigations, the Editors of Ann. Limnol. Where Ann. Limnol. -Int. J. Lim. is concerned, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…Bean plot representation of the Bray-Curtis dissimilarity between control and VectoBac®-treated areas for non-target invertebrate (A) and chironomid (B) communities within the study period in all sites. Overall, these results support the absence of relevant effects of Bti on aquatic food webs, as already evidenced by a number of field studies in wetlands (Painter et al, 1996;Blum et al, 1997;Balcer et al, 1999;Niemi et al, 1999;Lagadic et al, 2014;Fayolle et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Bean plot representation of the Bray-Curtis dissimilarity between control and VectoBac®-treated areas for non-target invertebrate (A) and chironomid (B) communities within the study period in all sites. Overall, these results support the absence of relevant effects of Bti on aquatic food webs, as already evidenced by a number of field studies in wetlands (Painter et al, 1996;Blum et al, 1997;Balcer et al, 1999;Niemi et al, 1999;Lagadic et al, 2014;Fayolle et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…More importantly, Duguma et al (2015) demonstrated that the reduced grazing pressure resulting from the reduction of mosquito larvae populations did not enhance microalgal biomass. This supports the absence of a top-down regulation of microorganism communities by mosquito larvae (Su and Mulla, 1999a;Fayolle et al, 2015).…”
Section: Introductionsupporting
confidence: 70%
“…They reported reduced clutch size and fledgling survival of house martins ( Delichon urbicum ), which they explained as an indirect effect of the use of Bti spray, correlating the use of the spray with decreased availability of certain house martin prey (Nematocera and the spiders and dragonflies that feed on them). This study was criticized for having its reference sites too far from its study sites, and a later study by Lagadic et al in a different area of France did not find any effects as a result of the application of Bt sprays, in agreement with a number of other studies .…”
Section: Effects Of Bt Toxins On Aquatic Organismssupporting
confidence: 77%
“…israelensis (Bti) and Bacillus sphaericus (Bs), are effective larvicides against mosquitoes (Walker and Lynch 2007). The use of Bti has demonstrated no harm to non-target organisms, which can be attributed to the specificity of its endotoxins (Gwal et al 2015), as well as no harm to the environment due to its low persistence under field conditions (Davis and Peterson 2008, Tetreau et al 2012, Fayolle et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In mosquitoes, the protein crystals bind to specific receptors exposed on the surface of the plasma membrane and then insert into the membrane, creating lytic pores in microvilli of apical membranes (Aronson and Shai 2001) that disturb the cell's osmotic balance, resulting in cell lysis and consequently death of the larvae (De Maagd et al 2001, Bravo et al 2007. The low persistence of Bti toxins under field conditions (Tetreau et al 2012) makes Bti an ecofriendly larvicide even when used in repeated treatments from three to seven years (Fayolle et al 2016). This rapid degradation, however, necessitates repeated applications of the larvicide for effective control of target organisms.…”
Section: Introductionmentioning
confidence: 99%